Cloud computing for digital libraries - Poulo, Lebeko Bernard Nkoebele (Department of Computer Science, 2015)
Information management systems (digital libraries/repositories, learning management systems, content management systems) provide key technologies for the storage, preservation and dissemination of knowledge in its various forms, such as research documents, theses and dissertations, cultural heritage documents and audio files. These systems can make use of cloud computing to achieve high levels of scalability, while making services accessible to all at reasonable infrastructure costs and on-demand. This research aims to develop techniques for building scalable digital information management systems based on efficient and on-demand use of generic grid-based technologies such as cloud computing. In particular, this study explores the use of existing cloud computing resources offered by some popular cloud computing vendors such as Amazon Web Services. This involves making use of Amazon Simple Storage Service (Amazon S3) to store large and increasing volumes of data, Amazon Elastic Compute Cloud (Amazon EC2) to provide the required computational power and Amazon SimpleDB for querying and data indexing on Amazon S3. A proof-of-concept application comprising typical digital library services was developed and deployed in the cloud environment and evaluated for scalability when the demand for more data and services increases. The results from the evaluation show that it is possible to adopt cloud computing for digital libraries in addressing issues of massive data handling and dealing with large numbers of concurrent requests. Existing digital library systems could be migrated and deployed into the cloud.